KAJIAN KRIMINOLOGI TERHADAP KEJAHATAN BEGAL DI KOTA SAMARINDA - Muhammad Laksamana dan Dina Paramitha Hefni Putri (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2020)
Begal motor action in the city of Samarinda increasingly disturbing the public, they acted not knowing the time and place. The intensity has also increased sharply. However, there has been no preventive efforts by the police on a large scale to ensure that Samarinda is free from the "colonialism" of thugs. What factors caused the crime of begal in Samarinda City.How is the effort made by law enforcers to deal with the crime of begal in Samarinda City The type of research used in this study is empirical legal research, which is a legal research method that looks directly at the field dataThe results of the research and discussion of the factors causing the occurrence of begal are, Economic Factors (perpetrators want to pay off debts to their own families), Factors of Reason Weaknesses Weaknesses reasoning power of perpetrators who make them choose the wrong choice between two choices. Weak perpetrators' reasoning power, which is sometimes found perpetrators still a student, Weaknesses Faith Factors Lack of planting religious values by parents towards children from an early age and the environment that is less supportive makes a child, especially teenagers at school age, very vulnerable to moral development or akhlaknya, Drug Addiction Factor some Actors said he always felt restless and could not concentrate properly when not consuming methamphetamine. There are three ways that countermeasures can be made against crime, namely, pre-emptive, preventive and repressive